2017
DOI: 10.1097/cji.0000000000000179
|View full text |Cite
|
Sign up to set email alerts
|

NK Cell–derived Exosomes From NK Cells Previously Exposed to Neuroblastoma Cells Augment the Antitumor Activity of Cytokine-activated NK Cells

Abstract: Immune cell-derived exosomes can increase immunity against tumors. In contrast, tumor-derived exosomes can reduce the immunity and can change the tumor microenvironment to further develop and provide metastasis. These effects take place by an alteration in the innate and adaptive immune cell functions. In this experiment, we studied the natural killer (NK) cells' effectiveness on tumor cells after expansion and thereafter incubated it with exosomes. The exosomes were derived from 2 populations of NK cells: (1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
95
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(103 citation statements)
references
References 46 publications
2
95
0
Order By: Relevance
“…They have been the focus of more than 150 cellular-based immunotherapy clinical trials as of March 2017 (clinicaltrials.gov). The antitumour behaviour of NK cells has been harnessed to treat hematologic malignancies that include acute myeloid leukaemia, acute lymphoblastic leukaemia multiple myelomas [4], solid tumours such as melanoma [5,6], breast cancer [7,8], thyroid cancer [2] and glioblastoma [1,9]. Because of the low number of NK cells in peripheral or cord blood, immune cell therapy with NK cells requires an ex vivo expansion process to achieve relevant numbers that express activation markers, natural cytotoxicity receptors (natural-killer group 2, member D [NKG2D], NKp44, Fas ligand [FasL], etc.)…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…They have been the focus of more than 150 cellular-based immunotherapy clinical trials as of March 2017 (clinicaltrials.gov). The antitumour behaviour of NK cells has been harnessed to treat hematologic malignancies that include acute myeloid leukaemia, acute lymphoblastic leukaemia multiple myelomas [4], solid tumours such as melanoma [5,6], breast cancer [7,8], thyroid cancer [2] and glioblastoma [1,9]. Because of the low number of NK cells in peripheral or cord blood, immune cell therapy with NK cells requires an ex vivo expansion process to achieve relevant numbers that express activation markers, natural cytotoxicity receptors (natural-killer group 2, member D [NKG2D], NKp44, Fas ligand [FasL], etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Because of the low number of NK cells in peripheral or cord blood, immune cell therapy with NK cells requires an ex vivo expansion process to achieve relevant numbers that express activation markers, natural cytotoxicity receptors (natural-killer group 2, member D [NKG2D], NKp44, Fas ligand [FasL], etc.) and cytokines (tumour necrosis factor-alpha [TNF-a], granzyme A and B, perforin) [2,4,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Innate immune cells, such as NK cells, neutrophils, mast cells (MCs), macrophages, and eosinophils, and adaptive immune cells, including DCs, T cells, and B cells, derived from exosomes can directly interact with cancer cells and uptake by tumor cells can induce different types of immune responses [26,27]. Accumulating evidence has shown that EVs derived from immune cells can promote pro-tumor and antitumor immunity, which suggests a complex relationship between the immune cell-derived EVs and the immune system [28][29][30][31]. NK cells that were previously exposed to neuroblastoma (NB) can secrete exosomes containing NK cell receptors, such as CD56, KIR2DL2, and NKG2D receptors, which can subsequently stimulate normal NK cells, generating greater and more e cient cytotoxicity against NB tumor cells [30].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has shown that EVs derived from immune cells can promote pro-tumor and antitumor immunity, which suggests a complex relationship between the immune cell-derived EVs and the immune system [28][29][30][31]. NK cells that were previously exposed to neuroblastoma (NB) can secrete exosomes containing NK cell receptors, such as CD56, KIR2DL2, and NKG2D receptors, which can subsequently stimulate normal NK cells, generating greater and more e cient cytotoxicity against NB tumor cells [30]. CD8+ T cell-derived exosomes with membrane expression of Fas ligand (FasL) can promote invasion and metastasis of Fas+ tumor cells through matrix metalloproteinase-9 (MMP-9)mediated degradation of extracellular matrix proteins [28].…”
Section: Discussionmentioning
confidence: 99%